Impact of Technology on Service Quality in the Banking Industry: A Study of Bank Clients’ Perspectives - Prasanna Jung Karki (Journal of Corporate Finance Management and Banking System ( JCFMBS) ISSN : 2799-1059, 2022)
The purpose of this study was to examine the relationship between the impacts of technology on service quality in the banking industry to determine which TRM dimension can potentially have the strongest influence on service quality of the banking industry. Data were gathered using a survey instrument, which was distributed among bank clients. The data were statistically analyzed using structural equation modeling with SPSS. The findings show that reliability, efficiency, and ease of use; responsiveness and communication; and security and privacy. A total of 450 populations from which 400 respondents participated in this study. Knowing the relative importance of service quality dimensions can help the banking industry focus on what satisfies customers the most. The goal of the study was to measure the relationship between perceived ease of use, perceived usefulness of technology, and attitude towards technology, behavioral intentions, and service quality in the banking industry. There is a significant negative relationship between Service Quality in the Banking Industry and Attitude towards Technology There is a significant negative relationship between Service Quality in the Banking Industry and Attitude towards Technology.